The impact of a previous tubal ectopic pregnancy on live birth and perinatal outcomes in vitrified-warmed cycles. Issue 6 (December 2022) - Wei, Mengjie; Feng, Guangen; Mao, Xiaoyan; Wu, Ling; Chai, Weiran; Zhang, Jie
Abstract: Research question: Does a previous history of naturally conceived tubal ectopic pregnancy (TEP) affect subsequent pregnancy and perinatal outcomes when a freeze-all policy is applied? Design: A large retrospective study was performed involving women who had undergone their first frozen-thawed embryo transfer (FET) cycles, using vitrified-warmed embryos, from January 2013 to April 2018 at a tertiary care centre. Participants were divided into two groups: a study group consisting of women with a history of TEP preceding IVF, and a control group consisting of women without an initial TEP. The live birth rate (LBR) and perinatal outcomes were evaluated via a propensity score matching method. Results: A total of 23, 270 women were included for potential analysis and finally 2168 pairs of women were generated for comparison after propensity score matching. The LBR in the study group was similar to that in the control group (45.7% versus 44.0%, P = 0.259). No differences were noted regarding rates of ectopic pregnancy (5.4% versus 4.1%, P = 0.122), miscarriage (11.5% versus 13.5%, P = 0.158) or intrauterine implantation (35.8% versus 35.8%, P = 0.974) between the groups. Regarding birth outcomes, the mean gestational age and birthweight and the incidences of preterm birth and low birthweight were comparable between the groups for both singletons and twins. Conclusions: The present study demonstrated that a prior history of TEP was not associated with adverse reproductive and perinatal outcomes in subsequent FET cycles. With the increasing utilization of FET globally, these results are important as they can help guide physicians during patient counselling.